2020
DOI: 10.1002/mco2.48
|View full text |Cite
|
Sign up to set email alerts
|

A cyclic peptide retards the proliferation of DU145 prostate cancer cells in vitro and in vivo through inhibition of FGFR2

Abstract: In malignancies, fibroblast growth factor receptors (FGFRs) signaling is reinforced through overexpression of fibroblast growth factors (FGFs) or their receptors. FGFR2 has been proposed as a target for cancer therapy, because both the expression and activation of FGFR2 are boosted in various malignant carcinomas. Although several chemicals have been designed against FGFR2, they did not exhibit enough specificity and might bring potential accumulated toxicity. In this study, we developed an epitope peptide (P5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…We have focused on investigating the roles of FGFs and FGFRs for years [ 37 – 41 ] and recently demonstrated that an endogenous FGFR2 inhibitory oligopeptide (P5), which is degraded from the basic fibroblast growth factor (bFGF, also known as FGF2) in vivo, effectively inhibits its downstream signalling. Importantly, P5 is a naturally occurring endogenous molecule that exhibits biological activities without terrible side effects [ 42 ]. This discovery of mild FGFR inhibitors with negligible toxicity will broaden the possible applications, especially for nonlethal inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…We have focused on investigating the roles of FGFs and FGFRs for years [ 37 – 41 ] and recently demonstrated that an endogenous FGFR2 inhibitory oligopeptide (P5), which is degraded from the basic fibroblast growth factor (bFGF, also known as FGF2) in vivo, effectively inhibits its downstream signalling. Importantly, P5 is a naturally occurring endogenous molecule that exhibits biological activities without terrible side effects [ 42 ]. This discovery of mild FGFR inhibitors with negligible toxicity will broaden the possible applications, especially for nonlethal inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…FGFR2, a receptor for the cytokine FGF10, is a key regulator of bone development and cancer. 48 Deletion of Fgfr2 isoforms results in osteogenesis dysfunction, suggesting its crucial role in bones. 3,[49][50][51] In this study, we discovered that FGFR2 is a potential substrate of OTUB1.…”
Section: Discussionmentioning
confidence: 99%
“…Although exogenous designed peptites have been shown promising therapeutic potentials [ 26 ], our understanding on cellular endogenous micropeptides remains very limited. In this study, we found that LINC00998, a gene initially annotated as a lncRNA, encodes a membrane‐integrated micropeptide named SMIM30.…”
Section: Discussionmentioning
confidence: 99%